The Idea of Progress: Meaning and Implications of Islam Berkemajuan in Muhammadiyah - Syamsul Arifin; Syafiq A Mughni; Moh Nurhakim (Al-Jami'ah: Journal of Islamic Studies, 2022)
Muhammadiyah is an Islamic religious organization founded in 1912 that has survived for more than a century in Indonesia. The survival and dynamic development of Muhammadiyah has inspired exploratory studies revealing the concomitant factors behind the proliferation of Muhammadiyah, one of which is the idea of Islam Berkemajuan (progressive Islam). This study relies mostly on the official documents and individual works published before and after the coinage of the terminology in the early 2000s. This study approaches the subject by systematically and critically constructing the historical and theological perspectives. This research shows that Islam Berkemajuan finds its roots in progressivice Islamic discourse among Muslim intellectuals and activists in early twentieth-century Indonesia. The idea of progress then serves as an intellectual response to social, political, and economic plight of Indonesians under Dutch colonial rule. In addition, the idea of progress is also particularly found in the discourse among inner circles of Muhammadiyah to advance the position of Muslims. Islam Berkemajuan was founded on theological grounds. In this, the teaching of Ahmad Dahlan on surah al-‘Ashr and surah al-Ma’un has become a strong inspiration behind Muhammadiyah’s commitment to using religious and rational understanding in teaching and action, developing education, health services, economic development, empowerment, philanthropy, and humanitarian action. [Muhammadiyah adalah organisasi keislaman di Indonesia yang berdiri sejak 1912 dan telah bertahan lebih dari seabad. Keberlangsungan dan dinamika perkembangan Muhammadiyah telah menginspirasi kajian eksploratif yang mencerahkan seiring faktor dakwah Muhammadiyah, salah satunya ide tentang Islam Berkemajuan. Tulisan ini sebagian besar berdasar dokumen resmi lembaga dan publikasi personal tentang Muhammadiyah baik sebelum dan sesudah terminologi ini muncul di awal tahun 2000an. Tulisan ini menggunakan pendekatan sistematis dan konstruktif kritis pada perspektif sejarah dan teologis organisasi ini. Tulisan ini ingin menunjukkan bahwa Islam Berkemajuan berakar pada progresifitas diskursus keislaman diantara intelektual dan aktivis muslim Indonesia awal abad 20. Ide kemajuan kemudian berkembang sebagai respon intelektual terhadap memburuknya sosial, ekonomi dan politik Indonesia dimasa kolonial Belanda. Ide kemajuan juga sebagian berkembang dilingkungan internal Muhammadiyah untuk mendorong posisi muslim Indonesia. Islam berkemajuan juga mempunyai landasan teologisnya dalam ajaran Ahmad Dahlan terkait surah al-‘Ashr dan surah al-Ma’un. Hal ini menjadi inspirasi kuat selain komitmen Muhammadiyah menggunakan agama dan pemahaman rasional dalam ajaran dan aksi, pengembangan pendidikan, pelayanan kesehatan, kesejahteraan ekonomi, pemberdayaan, filantropi dan aksi kemanusiaan.]